Analysis Study Of The Sam'iyah Wa Syafawiyah Method Concept In Learning Arabic Language At The Madrasah Tsnawiyah Level - Fathur Rusydi Amar (International Journal of Technology and Education Research, 2023)
The selection of the right method is expected to grow various student activities in connection with the teacher's teaching activities, so that they can achieve what is expected in the teaching and learning process. It can also encourage students to achieve optimal performance. Once again, among the methods of teaching Arabic that have been applied, each has advantages and disadvantages. Initially, the translation method was considered the most suitable for the ability to read effectively and understand the content. then came the Aural Oral Approach Method (Sam'iyah Wa Syafawiyah) which was once considered the most effective because it is based on linguistic principles which are expected to be able to answer and overcome various problems in the process of teaching and learning Arabic whose main goal is for students to have language skills or Arabic language skills properly and correctly. Thus, the purpose of teaching Arabic should refer to efforts to foster and develop the four aspects of language skills in question, namely the ability to listen, speak, read, and write with the hope that students are able to understand the language well through hearing or writing.